An Analysis of Factors Affecting Student Dropout: The Case of Tunisian Universities. Issue 2 (April 2022) - Srairi, Samir
The purpose of this paper is to analyze the determinants of university dropout in the first year of bachelor programs at Tunisian universities. We consider 160 higher education institutions with an average of 671 bachelor study programs per year from 2013 to 2018. Using several econometric models (pooled ordinary least square, fixed effect model, and random effect model), we regress student dropout rate on four categories of indicators: student characteristics, and institutional, contextual, and external factors. The estimation results suggest that the institutional characteristics have a significant impact on dropouts. The findings show that student–staff ratio has a positive influence on student dropout. We also find a negative association between staff quality and dropout rate. In addition, the analysis reveals the importance of contextual factors such as university accommodation in helping students to complete university education. Finally, regression also indicates a significant and positive interaction between unemployment rate and the dropout rate.